A comparison of health informatics education in the USA. (1st August 2019) - Erdil, D. Cenk
The need for health informatics professionals has been on the rise. Existing health informatics programs in the USA do not adequately equip students with relevant skills to address field-specific challenges. Thus, a skills gap arises between graduating health informatics professionals, and typical job requirements in many health informatics fields; and this gap has traditionally been addressed by employing graduates with computer science and engineering degrees. Moreover, graduate programs in many health informatics fields consistently offer less credits in computer science and information technology, compared to other informatics fields. This article provides a basic analysis of both undergraduate and graduate programs in health informatics in the USA. It highlights the differences across common informatics programs in medical sciences, and proposes more STEM-focused undergraduate degree options to complement existing undergraduate programs to have an immediate effect, which could provide students proper training to help narrow this technology-specific skills gap.